2021
DOI: 10.3389/fendo.2021.706532
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disrupting Chemicals and Reproductive Health in Boys and Men

Abstract: Male reproductive health has declined as indicated by increasing rates of cryptorchidism, i.e., undescended testis, poor semen quality, low serum testosterone level, and testicular cancer. Exposure to endocrine disrupting chemicals (EDCs) has been proposed to have a role in this finding. In utero exposure to antiandrogenic EDCs, particularly at a sensitive period of fetal testicular development, the so-called ‘masculinization programming window (MPW)’, can disturb testicular development and function. Low andro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 299 publications
(341 reference statements)
0
36
0
3
Order By: Relevance
“…Two patients (patients 1 and 6) carried SALL1 and SPECC1L mutations at the same time, which are involved in syndromes including hypospadias, but the role of these two mutations in the two patients may need to be further studied. On the other hand, endocrine disrupters like pesticide could also increase the risk of hypospadias ( 46 ), the phenomenon of CHH complicated with hypospadias needs more observation and research.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients (patients 1 and 6) carried SALL1 and SPECC1L mutations at the same time, which are involved in syndromes including hypospadias, but the role of these two mutations in the two patients may need to be further studied. On the other hand, endocrine disrupters like pesticide could also increase the risk of hypospadias ( 46 ), the phenomenon of CHH complicated with hypospadias needs more observation and research.…”
Section: Discussionmentioning
confidence: 99%
“…Best understood in rodent models, endocrine disruptor chemical exposures in the interval following sex determination and prior to birth have repeatedly been shown to increase the incidence of conditions including reduced anogenital distance, hypospadias, cryptorchidism and reduced germ cell numbers ( 13 15 ). These outcomes have been explored in data collected from boys and men, and from cultures of human fetal testes ( 16 18 ), with a growing understanding that not only exposure to endocrine disruptor chemicals, which can also include common pharmaceuticals, may negatively impact fetal and postnatal development. These agents can alter steroid composition and levels and may thereby influence local events in the testis.…”
Section: Dogma Relating To Fetal Testis Biology: Moving and Stationar...mentioning
confidence: 99%
“…Zamkowska et al 8 . showed consistency between semen parameter worsening and pyrethroids (PYRs) and organophosphates (OPs), while Rodprasert et al 9 . confirmed the effects of OPs and questioned those of organochlorines (OCs).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, two other reviews dealing with endocrine-disrupting chemicals (EDCs), including some types of pesticides, were published. Zamkowska et al 8 showed consistency between semen parameter worsening and pyrethroids (PYRs) and organophosphates (OPs), while Rodprasert et al 9 confirmed the effects of OPs and questioned those of organochlorines (OCs).…”
mentioning
confidence: 99%